Maternal Zika virus exposure and neurodevelopmental outcomes: A longitudinal study of preschool children in the ZIKAlliance Colombian Cohort - Víctor Herrera; María Consuelo Miranda; Anyela Lozano-Parra; Diana Niño; Luis Ángel Villar; Rosa Margarita Gélvez Ramírez; Thomas Jaenisch; Laura Pezzi; Claudia Acevedo; Jürg Niederbacher (PLoS ONE, 2026)
Background Zika virus (ZIKV) infection has been inconsistently associated with neurodevelopmental delay (ND). We aimed to compare the incidence of ND between ZIKV-exposed and ZIKV-unexposed children within the ZIKAlliance (ZA) cohort, in Colombia, assessed 2 years after birth (2018–2021). Methods We performed a neurodevelopmental evaluation on normocephalic children (aged 40–72 months) from the ZIKAlliance cohort. Children were classified as ZIKV-exposed (maternal positive RT-qPCR or virus neutralization test – VNT) or unexposed (maternal negative IgG ELISA or VNT in paired antenatal samples). A trained psychologist, blinded to exposure status, administered the Denver Developmental Screening Test II (DDST-II). Children were considered at ND risk if they presented ≥1 delay or ≥2 cautions in one or more areas, within their age range in the DDST-II scale. Inconclusive initial tests were re-evaluated. Adjusted odds ratios were estimated using logistic regression. Results We analyzed conclusive DDST-II results from 153 children (mean age: 4.7 years; 53.8% male). Overall, 57.2% (n = 83) were classified as cases of ND. Children with ND were more likely to be male (61.4% versus 43.5%) and less likely to attend daycare or school (42.2% versus 11.3%) than children with normal development. After adjusting for child age, sex, household size, and education, the association between in utero ZIKV exposure and ND was not statistically significant (OR = 0.71; 95% CI: 0.32–1.59, p = 0.320). However, children attending daycare or school had a significantly lower risk of ND compared to those who stayed at home. Conclusions Prenatal ZIKV exposure was not associated with ND in this cohort of normocephalic preschool children. Instead, attending a community daycare or school emerged as a significant protective factor against developmental delays.